Organization of the Six-Cylinder Tractor Diesel Working Process - Kukharonak, Heorhi; Klesso, Mikhail; Predko, Andrei; Telyuk, Dmitry; Vovk, Yuriy; Lyashuk, Oleg (International Journal of Integrated Engineering, 2021)
The purpose of the work is the organization of the six-cylinder diesel engines (with a power of 116 and 156 kW) working process with exhaust gas recirculation. The following systems and components were used in the experimental configuration of the engine: Common Rail BOSÐ¡H accumulator fuel injection system with an injection pressure of 140 MPa equipped with electro-hydraulic injectors with 7-hole nozzle and a 500 mm3 hydraulic flow; direct fuel injection system with MOTORPAL fuel pump with a maximum injection pressure of 100 MPa, equipped with MOTORPAL and AZPI five-hole nozzle injectors; two combustion chambers with volumes of 55 and 56 cm3 and bowl diameters of 55 and 67.5 mm; cylinder heads providing a 3-4 swirl ratio for Common Rail system, 3.5-4.5 for mechanical injection system; recirculation rate was set by gas throttling before the turbine using original design rotary valve. The tests were conducted at characteristic points of the NRSC cycle: minimum idle speed 800 rpm, maximum torque speed 1600 rpm, rated power speed 2100 rpm. It is established: achievement of emission standards for the 116 kW diesel engine is possible with the use of direct-acting fuel equipment and a semi-open combustion chamber; on the 156 kW diesel - using the Low Cost type common Rail fuel supply system and an open combustion chamber.